Uma experiência sobre o ensino da matemática no ensino médio sob a perspectiva da utilização de problemas da OBMEP - Guimarães, João Paulo Silva (2020)
In this work we present the idealization, application and discussion of the use of 5 OBMEP problem versions in the form of activity sheets using manipulable material and technological resources in mobile phones.